Integrace klientů ze zařízení pro výkon ústavní výchovy do společnosti – zkušenosti z pohledu pracovníka tohoto typu zařízení - Křížová, Soňa (Univerzita Pardubice, 2009)
This contribution is devoted to the practical experience of the worker of school institutions for institutional education with the integration of leaving clients to the usual life. It deals about of educational programmes of these institutions and its contact to the practical life after being of age. It revers to the necessity of co-operation of all institutions to nocomplicated client‘s integration to the usual life.
Keywords: institutional education; secure training center; educational programme; key competencies